Mazabraud- und McCune-Albright-Syndrom in Assoziation: ein Fall zweier sehr seltener tumororthopädischer Entitäten - Schwarze, Martin; Weber, Marc-André; Mechtersheimer, Gunhild; Lehner, Burkhard; Renker, Eva Kristin (Der Orthopäde, 2017)
Abstract: We report on a 47-year-old woman with unilateral fibrous dysplasia and three intramuscular masses. Medical imaging revealed possible...